EVALUASI KANDUNGAN LIGNIN DAN TANNIN PADA KULIT PISANG GOROHO (Musa acuminafe, sp) FERMENTASI SEBAGAI PAKAN TERNAK AYAM RAS PETELUR - Fatma Husain (Jambura Journal of Animal Science, 2020)
The research aimed at investigating the content of lignin and tannin in the peel of goroho banana fermented as laying hens’ feed. It was arranged based on a completely randomized design with 4 treatments and 3 repetitions. The treatments were P0= goroho banana’s peel without fermentation, P1= goroho banana’s peel fermented with 0,3% Rhyzopus olygosporus, P2= goroho banana’s peel fermented with 0,3% Trichoderma viride, P3= goroho banana’s peel fermented with 0,15% Rhyzopus olygosporus + 0,15% Trichoderma viride. The data were analyzed, occupying the least significance test. Findings revealed that the nutrition of goroho banana’s peels fermented as laying hens’ feed has significant differences with lignin and tannin (P 0.01). The lowest lignin content was in treatment P3 (16,23), while the lowest tannin content was in treatment P1 (0,20). It can be concluded that the goroho banana’s peel that can be utilized as laying hens’ feed was the peel that had been fermented with 1,5% Rhyzopus olygosporus + 1,5% Trichoderma viride containing 16,23% lignin. However, the peel fermented with Rhyzopus olygosporus contained tannin for 0,20%.